Pengelolaan Pelatihan Agribisnis Pisang Kirana Dalam Meningkatkan Kompetensi Petani Di Desa Gondoruso Kabupaten Lumajang - Hendrayani, Ragil Nurin; Hendrawijaya, Arief Tukiman; Hilmi, Muhammad Irfan (Learning Community : Jurnal Pendidikan Luar Sekolah, 2023)
The potential of the Lumajang area in the food agriculture sector is the Kirana banana. Lumajang city, which is famous for producing the best Kirana bananas, has not been supported by a large production level and superior banana quality, so that this potential is not seen as a promising job field for farmers. This study was designed to follow the rules of qualitative research using a case study research design, the selection of research sites was carried out using a purposive area technique based on certain considerations. With 3 informants using purposive sampling technique, research informants are agribusiness training managers, training instructors, and Kirana banana farmers. Data collection techniques are through unstructured interviews, participatory and unstructured observations, as well as documentation in the form of photos, notes, and voice recordings. In analyzing research data, the researcher adopts a qualitative approach which is generally inductive. The results showed that the management activities in this training applied George R. Terry's theory with 4 management functions, namely planning, management, implementation, and evaluation. Related to improving the competence of farmers, this training discusses the knowledge, skills, and attitudes that must be possessed by farmers